“I Didn’t Question It, That Was Normal to Me”: An Auckland New Zealand Exploratory Study into Tongan Attitudes Towards Intimate Partner Violence Against Women - Fonise, Ma'ata (Auckland University of Technology, 2023)
Intimate Partner Violence (IPV) occurs in every country, among various groups of people from all socio-economic statuses, and has detrimental effects on the lives of those on the receiving end of the violence (Rivas et al., 2019; Signorelli et al., 2012; WHO, 2021). Although any person can be a victim of IPV, women are disproportionately on the receiving end compared to any other group of people. Furthermore, IPV is a significant social problem concerning the Pacific community in NZ, with statistics suggesting that Pacific and Māori women have a higher risk of IPV in comparison to Asian or European women (Bird et al., 2021; Fanslow et al., 2010; Malatest International, 2021). Attitudes toward IPV have been found to influence the normalisation and perpetration of violence (Copp et al., 2019; Simmons, 2008) and therefore, this thesis is an exploratory study to understand what Tongan attitudes towards IPV against women are, significant factors that contribute or influence IPV and what possible strategies could be implemented to mitigate and prevent IPV in Tongan communities. A total of seven participants, who currently reside in Auckland and were between 22 and 39 years old, participated in a talanoa for this study. Findings suggest that although participants had not come across the term IPV, they were aware of other known concepts such as domestic abuse, domestic violence and family harm. Furthermore, the participants perceived physical, emotional, and verbal abuse to be a form of IPV, but, interestingly, most participants did not identify sexual abuse as IPV. Additionally, participants believe factors such as financial strain, cultural and church obligations indirectly contribute to IPV against women. Most participants believe encouraging support networks and targeted programmes that address underlying factors related to IPV and implementing culturally appropriate counselling services that are affordable and accessible in the community would help in reducing IPV in the Tongan community. Participants also believe these strategies could be well implemented with the engagement of influential members of society, such as church ministers or religious leaders, due to churches’ significant impact on the Tongan community. A key limitation of this study is that the sample recruited was very small, and it is recommended that future research involves a larger sample and covers other New Zealand regions outside of Auckland.